TEST OF ACTIVITY OF BIOACTIVE COMPOUNDS IN EXTRACT FRACTION METHANOL SARGASSUM SP (ALGA CHOCOLATE) AS ANTI HEPATOTOKSIK - Nurfina Aznam; Sri Atun; Susila Kristianingrum (Jurnal Penelitian Saintek, 2001)
The objectives  of this  research  are  to  identify  whether  the  bioactivecompound of methanol fraction  extracts of Sargasum sp can be used as anti hepatotoxic and to determine the dose of such compound in order that  it  may  be  used as anti hepatotoxic.  The population  used  in  this research was 2-month male white rats with almost similar weight. 39 rats were  taken for  the samples.  Treating  CCl4  injection carried   out  the bioactive compound activity test and the treatment of these compound extracts was observed by examining the liver cell damage microscopically and analyzing the GPT content. Examination was a/so conducted to the control rats (without CCI4  injection and bioactive compound treatment). From the result of the research it can be concluded that methanol fraction extract of Sargasum sp may be used as anti hepatotoxic. It wasfound  that the bioactive compound activity appeared at the dose of 500 mglkg of weight with 5 times treatments.